Pemanfaatan Aplikasi Point Of Sale (POS) dalam Manajemen Resiko bagi UMKM Pekon Sumber Mulyo - Manan, Mohammad Athian; Samosir, Amril; Nurbaiti, Nurbaiti (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The rapid advancement of technology poses both opportunities and challenges for micro, small, and medium enterprises (MSMEs), particularly in managing business risks. This community service activity aimed to enhance the capability of MSME operators in Pekon Sumber Mulyo, Tanggamus Regency, in utilizing Point of Sale (POS) applications to manage operational risks effectively. The activity involved 40 participants, including MSME operators, community members, and village administrators. The methods implemented were presentations, simulations, and interactive discussions focusing on risk management, stock opname, and POS usage. The results indicated a significant increase in participants' understanding, reflected by an improvement in test scores from 60% to 85%. Participants also demonstrated readiness to adopt POS technology in their daily operations. The activity successfully introduced digital solutions to support MSME sustainability and competitiveness, marking a step forward in the digital transformation of local businesses.